Faktor-Faktor Risiko Tertular Flu Burung di Desa-Desa Kabupaten Klungkung, Bali (THE RISK FACTOR OF BIRD FLU CASES IN VILLAGES IN KLUNGKUNG REGENCY, BALI) - Temaja, I Gusti Ngurah Badiwangsa; Suartha, I Nyoman; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2013)
This study was carried  out to identify the risk factor of  bird flu cases in villages in Klungkung regency,Bali. The data were collected through observation and interviews using questionnaire to head of householdsin villages of which were officially recorded as infected and uninfected area of bird flu.  Data was analyzedusing chi-square test and odds ratio to see the relationship AI infection and risks factors, as well as howsignificance is the relationship between them. The study showed that the crucial risk factor to bird flucases in infected villages were ceremonies (odds ratio : 2.401) and traditional rituals (odds ratio 3.229).The occurrence to bird flu in both villages is significantly affected by the following fctors: (1) poultry forconsuming, ceremony, and traditional ritual from markets and collected poultry, (2) disposal of deadchicken in to the  river, (3) the operation of villages markets, (4) Trading of live  poultry, (5) Commercialpoultry livestock in respected villages, (6) herding duck after rice harvesting, (7) frequency  of traditionalceremonies  in the villages.
Keywords: risk factor, bird flu, villages Key Words: risk factor, bird flu, villages